Compliance Of Thermal Comfort Parameters Within Students’ Dormitory, Residental And Pusat Islam Engineering Campus, Usm Based On Industry Code Of Practice On Indoor Air Quality (Icop) 2010 - Halili, Ummi Zulaikha Ahmad (Universiti Sains Malaysia, 2021)
This study was conducted to assess occupants’ satisfaction with their surrounding temperature conditions. The study was carried out at three places which are students’ dormitory, residential and prayer hall of Pusat Islam Engineering Campus, USM. It entailed determining the compliance of thermal comfort parameters; temperature, relative humidity and air movement. The parameters are then used as input in the Center for the Built Environment (CBE) Thermal Comfort Tool to obtain Predicted Mean Value and Predicted Percentage Dissatisfied for ASHRAE Standard-55. The monitoring for this study was conducted for three hours in a three-time period; 6 A.M. - 9 A.M., 11 A.M. - 2 P.M. and 5 P.M. - 8 P.M. for students’ dormitory and residential. For monitoring at Pusat Islam, it was conducted in two slots; 11 A.M. - 2 P.M. and 6 P.M. - 10 P.M., and it was assessed during Ramadan, where the Muslims perform Teraweh prayer. Overall, the finding indicates that most of the time, the thermal comfort parameters do not comply with the ICOP limit. This is due to the poor design of students’ dormitory where the plan itself does not promote cross-ventilation, causing discomfort towards the occupants.